Cybersecurity Vulnerabilities in Digital Business: Challenges, and Novel Directions for Resilience (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
Digital transformation increases cybersecurity vulnerabilities that threaten organizational resilience and stakeholder trust. This study analyzes cybersecurity vulnerabilities in digital business through a review of current open access literature. Findings reveal 89% of companies experience web application vulnerabilities, 93% have hosting misconfigurations, and 46% of employees reuse breached passwords. Artificial Intelligence (AI) exacerbates threat sophistication but offers resilience strategies through advanced detection and dynamic risk management. Case studies of SAP NetWeaver zero-day exploitation (CVE-2025-31324) and zero-trust architecture implementation demonstrate the effectiveness of AI-based threat mitigation. The research recommends integrating AI-driven cybersecurity tools, enhancing supply chain security, and developing cyber-aware organizational cultures to maintain business resilience against increasingly complex cyber threats. The study emphasizes cross-disciplinary approaches integrating technology, business strategy, and human factors as essential for sustainable cyber resilience in digital business environments.
Keywords: cybersecurity vulnerabilities; digital business; cyber resilience; AI-driven security; zero- trust architecture